1997
DOI: 10.1046/j.1365-3156.1997.d01-346.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of acute measles infections in hospitalized children in Zambia

Abstract: SummaryLaboratory diagnosis of measles infection is rarely performed in developing countries and tends to depend on clinical symptoms alone. We evaluated detection of immunoglobulin M (IgM) antibodies for confirmation of acute measles infection in Zambia. In 149 hospitalized children with clinical diagnosis of measles, IgM antibodies were detected in 88.6% (132/149). The IgM-positive rate increased with time after onset of skin rash and all samples were positive after 4 days. In addition to IgM antibody test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The WHO standard clinical cases definition was designed for maximum sensitivity at the expense of specificity for surveillance purposes and led to a correct diagnosis in 75% of measles cases in our field study population. Reports from other areas vary: in Zambia, a higher sensitivity of 86% (increasing to 100% after 4 days) was found among hospitalized children, who may have been more ill and therefore more likely to have measles than another viral illness which on average, as also observed in this study, runs a milder course (Oshitani et al . 1997).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The WHO standard clinical cases definition was designed for maximum sensitivity at the expense of specificity for surveillance purposes and led to a correct diagnosis in 75% of measles cases in our field study population. Reports from other areas vary: in Zambia, a higher sensitivity of 86% (increasing to 100% after 4 days) was found among hospitalized children, who may have been more ill and therefore more likely to have measles than another viral illness which on average, as also observed in this study, runs a milder course (Oshitani et al . 1997).…”
Section: Discussionsupporting
confidence: 60%
“…The WHO standard clinical cases definition was designed for maximum sensitivity at the expense of specificity for surveillance purposes and led to a correct diagnosis in 75% of measles cases in our field study population. Reports from other areas vary: in Zambia, a higher sensitivity of 86% (increasing to 100% after 4 days) was found among hospitalized children, who may have been more ill and therefore more likely to have measles than another viral illness which on average, as also observed in this study, runs a milder course (Oshitani et al 1997). An Australian study used notification to a public health unit as the entry criterion and found only 49% sensitivity using the slightly different CDC classification, which is identical to the WHO definition apart from requiring the fever to be >38.3°C and the rash to be present for at least 3 days (CDC 1990;Ferson et al 1995).…”
Section: Discussionsupporting
confidence: 56%
“…In a cohort study of almost 200 clinically diagnosed Sudanese measles patients, we recently found that in approximately 25% of these cases the clinical symptoms were not related to acute MV infection (6). Other studies reported between 12% and more than 50% falsely diagnosed measles cases (5,7,11,13,14), with an apparent inverse relationship with vaccination coverage.…”
mentioning
confidence: 94%
“…Despite the high coverage with measles vaccine in most parts of Africa, epidemics of measles still occur with reduced severity in an increasing proportion of older children previously immunized 17,20–22 . In general, the prodromal period in VMM is shorter.…”
Section: Discussionmentioning
confidence: 99%